Імітаційні випробування трактора ХТЗ-160У на основі польових циклів PowerMix - Ребров, Олексій Юрійович; Якунін, Максим Євгенович (Національний технічний університет "Харківський політехнічний інститут", 2021)
В роботі наведені результати імітаційних тягово-динамічних випробувань перспективного універсального трактора ХТЗ-160У, отримані на основі польових випробувальних циклів PowerMix. Наведена методика визначення ККД трактора в агрегаті з сільськогосподарським знаряддям, яка будується на складових балансу потужності, отриманих при усередненні результатів розрахунків за польовими випробувальними циклами PowerMix. За результатами розрахунків показників наведеної продуктивності, погектарної витрати палива, ККД трактора в агрегаті з сільськогосподарським знаряддям та ймовірності виконання агроекологічних вимог на території України визначені найбільш перспективні варіанти комплектації шинами трактора ХТЗ-160У.

The paper presents the results of simulation traction-dynamic tests of the promising universal tractor KhTZ-160U, obtained on the basis of PowerMix field test cycles. A technique for determining the efficiency of a tractor in an aggregate with an agricultural implement is given, which is based on the components of the power balance obtained by averaging the results of calculations for PowerMix field test cycles. Based on the results of calculating the indicators of reduced productivity, per hectare fuel consumption, the efficiency of a tractor in an aggregate with an agricultural implement and the likelihood of meeting agro-ecological requirements on the territory of Ukraine, the most promising options for equipping tractor KhTZ-160U with tires were determined. It is shown that the KhTZ-160U tractor has the best indicators of efficiency and environmental friendliness on dual tires 420/85R34 GoodYear 142 (A8), which can also carry out interrow tillage. The base tire 480/70R34 Voltyre 143 (A8) has the worst performance and cannot be recommended for implementation, as it meets agri-environmental requirements in only 18% of Ukraine. The 540/65R34 Mitas 148 (A8) has the highest performance rating and is therefore recommended as a base.
Simulation testing of the KhTZ-160U tractor based on PowerMix field cycles
Keywords: трактор; PowerMix; тягово-динамічні випробування; продуктивність; витрата палива; tractor; traction and dynamic tests; performance; fuel consumption